Zooplankton biomass, abundance and diversity in a shelf area of Portugal (the Berlenga Marine Natural Reserve). - Pardal, Miguel (2008)
During November 1997 and May 1998, zooplankton samples were collected with other environmental data along the shelf area of Berlenga marine natural reserve (MNR) (NW Portugal). Copepods contributed > 70 % to the total zooplankton community. In November the dominant species of copepods were Paracalanus parvus, Temora stylifera and Centropages chierchiae with larvaceans and the cladocerans Penilia avirostris also abundant. The meroplankton was dominated by echinoderms. In May the dominant species of copepods were Pseudocalanus elongatus and Acartia clausi, Centropages typicus, and Calanus helgolandicus, with barnacle larvae and the pisces larvae also abundant. The islands influence was represented in the results by the increase in diversity and meroplankton’s relative importance at the sampling stations in the vicinity of the islands.